2019
DOI: 10.1126/sciadv.aaw5296
|View full text |Cite
|
Sign up to set email alerts
|

Battery-free, fully implantable optofluidic cuff system for wireless optogenetic and pharmacological neuromodulation of peripheral nerves

Abstract: Studies of the peripheral nervous system rely on controlled manipulation of neuronal function with pharmacologic and/or optogenetic techniques. Traditional hardware for these purposes can cause notable damage to fragile nerve tissues, create irritation at the biotic/abiotic interface, and alter the natural behaviors of animals. Here, we present a wireless, battery-free device that integrates a microscale inorganic light-emitting diode and an ultralow-power microfluidic system with an electrochemical pumping me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
144
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 49 publications
0
144
0
Order By: Relevance
“…Recently, we introduced a soft, fully implantable optofluidic cuff system designed to deploy on peripheral nerves, with ultralow power requirements by use of miniaturized electrochemical micropumps for drug delivery (21). Here, we improve upon and adapt those ideas to establish a functional device that is able to interface with the brain.…”
Section: Significancementioning
confidence: 99%
“…Recently, we introduced a soft, fully implantable optofluidic cuff system designed to deploy on peripheral nerves, with ultralow power requirements by use of miniaturized electrochemical micropumps for drug delivery (21). Here, we improve upon and adapt those ideas to establish a functional device that is able to interface with the brain.…”
Section: Significancementioning
confidence: 99%
“…Furthermore, inspired by the iWEBS and considering functionally relevant factors such as mechanical tissue damage and efficient power transmission, the flexible µLED arrays were designed to be inserted into the subcranial space and efficiently illuminate a specific cortical domain. [102,103] This thin-film optical stimulator (15 µm thickness) was successfully inserted under a living mouse skull ( Figure 3b) and used to illuminate the cerebral cortex with blue light without any significant infection or inflammation (Figure 3c). In addition, these flexible µLEDs (30 × 30 arrays in 1 × 1 cm 2 ) can operate stably using a wireless power supply system, enabling continuous photostimulation in freely moving animals.…”
Section: Brain-compatible Writing Devicesmentioning
confidence: 99%
“…Reproduced under the terms and conditions of the CC‐BY license 4.0. [ 286 ] Copyright 2019, The Authors. Published by American Association for the Advancement of Science.…”
Section: Multimodal Microsystemsmentioning
confidence: 99%
“…In addition to applications in the brain, Zhang et al reported a fully implantable wireless optofluidic cuff system integrating PDMS‐based microfluidic channels and blue μ‐ILEDs for modulation of the peripheral nervous system (Figure 14f). [ 286 ] An electrochemical pumping mechanism is adopted to minimize power consumption and heat generation from the previously discussed thermally expanded pumping mechanism. The lightweight optofluidic cuff system allows for chronic modulation of targeted peripheral nerve activity in freely moving mice via localized drug delivery and optogenetic stimulation without damaging the associated peripheral nerve.…”
Section: Multimodal Microsystemsmentioning
confidence: 99%